Police dogs helping to fight crime - McGinty, Alice B. (New York, NY PowerKids Press, 1999)
Explores the selection, training, and uses of police dogs in fighting crime.
Includes index.
810L
Keywords: Police dogs -- Juvenile literature; Police dogs; Dogs